2018
DOI: 10.1038/s41467-018-05683-7
|View full text |Cite
|
Sign up to set email alerts
|

Wheat microbiome bacteria can reduce virulence of a plant pathogenic fungus by altering histone acetylation

Abstract: Interactions between bacteria and fungi have great environmental, medical, and agricultural importance, but the molecular mechanisms are largely unknown. Here, we study the interactions between the bacterium Pseudomonas piscium, from the wheat head microbiome, and the plant pathogenic fungus Fusarium graminearum. We show that a compound secreted by the bacteria (phenazine-1-carboxamide) directly affects the activity of fungal protein FgGcn5, a histone acetyltransferase of the SAGA complex. This leads to deregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
209
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(215 citation statements)
references
References 69 publications
(86 reference statements)
5
209
0
1
Order By: Relevance
“…The most effective way for wheat producers to manage and control FHB is by breeding resistant cultivars. Great efforts have been made to find FHB resistance genes and understand the genetic mechanism of the resistance [5][6][7][8][9]. The genetic mechanisms for FHB resistance are complex, and the genotype by environment interaction has very strong effects on trait expression [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The most effective way for wheat producers to manage and control FHB is by breeding resistant cultivars. Great efforts have been made to find FHB resistance genes and understand the genetic mechanism of the resistance [5][6][7][8][9]. The genetic mechanisms for FHB resistance are complex, and the genotype by environment interaction has very strong effects on trait expression [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For direct mechanisms, BCAs secrete growth‐enhancing phytohormones, solubilize soil minerals and fix atmospheric nitrogen to promote plant growth. Indirect mechanisms include antagonism that relieves the detrimental effects of phytopathogens, parasitism, nutrition depletion, eco‐niche competition, quorum quenching on pathogenic bacteria, induction of plant systemic resistance and suppression of the pathogenicity by metabolites produced by BCAs (Dong et al ., ; Kloepper and Ryu, ; Zhang et al ., ; Yi et al ., ; Chowdhury et al ., ; Chen et al ., ; Rahman et al ., ). Interestingly, studies have shown that an increasing complexity of the microbial consortia (bacteria, fungi and oomycetes together) can result in significantly better plant growth compared with any single or double formula (DurĂĄn et al ., ).…”
Section: Rhizomicrobiome Is Key To Plant Healthmentioning
confidence: 99%
“…On the other hand, the wide use of chemical pesticides raises serious concerns due to their detrimental side‐effects to the environment and human health (Cray et al ., ). Thereby, alternative environment‐friendly control methods such as applications of resistant cultivars, agricultural measures and biological control agents (BCAs) have become increasingly attractive and promising for controlling soil‐borne diseases (Lyon and Newton, ; Cray et al ., ; Chen et al ., ; Poudel et al ., ). BCAs are developed from plant beneficial microorganisms including bacilli, pseudomonads, agrobacteria, actinobacteria, streptomyces, saccharomycetes and trichodermaes, and are considered a feasible alternative to chemical pesticides due to their effectiveness in controlling particular soil‐borne diseases and their safe and eco‐friendly traits (for reviews see Weller, ; Vandenkoornhuyse et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…tritici, phenazine‐1‐carboxamide was more effective against tomato root rot than either PCA or its hydroxylated derivatives, and a hydroxylated PCA derivative was the most inhibitory in vitro to Alternaria brassicae . There are few reports of phenazine activity against foliar pathogens, but the commercial fungicide shenqinmycin, with PCA as its main active ingredient, is widely used in southern China to control sheath blight of rice and notably, phenazine‐1‐carboxamide produced by P. piscium on the heads of wheat infected with the head blight pathogen Fusarium graminearum has been shown to interfere with histone acetylation, suppressing fungal growth, virulence, and mycotoxin biosynthesis …”
Section: Model Systems In Pseudomonasmentioning
confidence: 99%